Demonstratives in cross-linguistic perspective - Levinson, Stephen C. 1947-; Cutfield, Sarah ca. 20./21. Jh; Dunn, Michael 1969-; Enfield, N. J. 1966-; Meira, Sérgio 1968- (Language, culture, and cognition, 2018)
Demonstratives play a crucial role in the acquisition and use of language. Bringing together a team of leading scholars this detailed study, a first of its kind, explores meaning and use across fifteen typologically and geographically unrelated languages to find out what cross-linguistic comparisons and generalizations can be made, and how this might challenge current theory in linguistics, psychology, anthropology and philosophy. Using a shared experimental task, rounded out with studies of natural language use, specialists in each of the languages undertook extensive fieldwork for this comparative study of semantics and usage. An introduction summarizes the shared patterns and divergences in meaning and use that emerge